Epidemiologic Investigation of a Varicella Outbreak in an Elementary School in Gyeonggi Province, Republic of Korea - Gipyo Sung; Jieun Jang; Kwan Lee (Children)
Background/Objectives: On 6 June 2023, two varicella cases were reported at a highly vaccinated elementary school in Gyeonggi Province, Republic of Korea. We investigated the outbreak to describe its transmission dynamics; quantify attack rates in school, household, and private-academy settings; and assess the impact of coordinated control measures. Methods: A case-series study included 89 teachers and students who had contact with suspected patients. Using case definitions, laboratory tests, questionnaires, and environmental assessments, we evaluated exposures and factors facilitating spread. Results: Varicella developed in 23 of 89 contacts (25.8%); laboratory confirmation was obtained in 2 (8.7% of cases). The mean incubation period was 13 days. Epidemic-curve and network analyses indicated that the outbreak began with a single index case and extended through household contacts and private educational facilities, ultimately involving multiple schools. Conclusions: Breakthrough transmission can occur even when single-dose coverage exceeds 95%, particularly as vaccine-induced immunity may wane over time. Poorly regulated extracurricular facilities, such as private academies, act as bridging hubs that amplify spread across grades and even between schools. For timely detection and control, these venues should be incorporated into routine varicella surveillance, and rapid, coordinated infection-control measures are required across all educational settings.